Spinel MnCo2O4 Nanoparticles Supported on Three‐Dimensional Graphene with Enhanced Mass Transfer as an Efficient Electrocatalyst for the Oxygen Reduction Reaction. Issue 16 (17th July 2018) - Zhang, Tingwei; Li, Zhongfang; Wang, Likai; Sun, Peng; Zhang, Zhixu; Wang, Suwen
Abstract: The rational design of highly efficient and durable oxygen reduction reaction (ORR) catalysts is critical for the commercial application of fuel cells. Herein, three‐dimensional graphene (3D‐G) is synthesized by the template method, which used coal tar pitch as the carbon source and nano MgO as the template. Then, spinel MnCo2 O4 is in situ supported on the 3D‐G by a facile hydrothermal method, giving MnCo2 O4 /3D‐G. The resultant MnCo2 O4 /3D‐G retains the multilayered mesoporous graphene structure where MnCo2 O4 nanoparticles are deposited on the inner walls of pores in the 3D‐G. The catalyst MnCo2 O4 /3D‐G shows high electrocatalytic activity with a half‐wave potential of 0.81 V versus reversible hydrogen electrode, which is clearly superior to those of MnCo2 O4 /reduced graphene oxide (0.78 V), MnCo2 O4 /carbon nanotubes (0.74 V), MnCo2 O4 /C (0.72 V), and 20 wt % Pt/C (0.80 V). The electron transfer number of MnCo2 O4 /3D‐G indicates a four‐electron process of ORR. The durability test demonstrates that the MnCo2 O4 /3D‐G catalyst has a much better durability than 20 wt % Pt/C. Our work makes an inspiring strategy to prepare high‐performance electrocatalysts for the development of fuel cells. Abstract : Three‐dimensional graphene (3D‐G) was synthesized by the template method. Then, spinel MnCo2 O4 was in situ supported on the 3D‐G. The resultant MnCo2 O4 /3D‐G retains the multilayered mesoporous graphene structure where MnCo2 O4 nanoparticles are deposited on the inner walls of pores in the 3D‐G. The catalyst MnCo2 O4 /3D‐G shows high electrocatalytic activity with a half‐wave potential of 0.81 V versus reversible hydrogen electrode.